(untitled) (Journal of Partial Differential Equations, 2002)
In this paper we establish the blow up of solutions to the quasilinear wave equation with a nonlinear dissipative term u_tt - M(||A^1/2u||²_2)Au + |ut|^βu_t = |u|^pu x ∈ Ω, t > 0